Rank-based predictive control for community microgrids with dynamic topology and multiple points of common coupling - Nun, Brevann (Kansas State University, 2021)
The devastating effects of climate change paired with increasing geopolitical tensions and rising energy needs have prompted the development and incorporation of renewable energy technologies with the bulk power system in recent decades. Rapid advancements in technologies such as solar photovoltaics (PV) and wind harvesting devices have led to the proliferation of distributed energy resources at the distribution level. Decreasing costs of renewable energy systems and the ever-present dangers of climate change facilitate an increase in the saturation of these resources at the grid edge. However, a high penetration of intermittent energy generation dependent on solar irradiance and wind speed, as well as limited storage availability, creates challenges of grid resiliency and stability. A potential solution to overcome the aforementioned operational challenges is to realize hierarchical grid clusters with flexible boundaries towards resilient operation of future power grids. These hierarchical grid clusters, forming the entire grid, are also known as a grid of microgrids or grid of nanogrids. Hierarchical clusters of distributed energy resources (DERs) forming a grid of microgrids can share power more efficiently. A microgrid can operate in grid-connected or islanded modes which provide resiliency by supplying local loads within the microgrid boundary during natural disasters or other anomalies in power grid. The flexible boundaries of these microgrids requires multiple points of common coupling (MPCC) with adjacent microgrids and the rest of the power network which makes their synchronization challenging. Thus, in a power grid comprising a network of microgrids and MPCC, control and synchronization of voltage source converters (VSCs) is paramount to ensure optimal performance without jeopardizing network stability. This thesis presents a rank-based model predictive controller (MPC) for VSCs operating in a community microgrid with dynamically changing topology representing the flexible boundary of the microgrid. The proposed framework enables a fully synchronized microgrid with the ability to connect multiple distributed VSC buses to a utility grid simultaneously through MPCC. In addition, the control scheme offers redundancy to grid-forming sources when islanded, attaining a higher margin of resiliency, robustness, and flexibility. The MPC framework features an adaptive ranking system that assigns operational modes to the VSCs, i.e. voltage control (grid-forming) or current control (grid-following), and defines leader-follower directionality for synchronization. Communication among VSCs is achieved using a topology-mirroring communication layer. The presented framework enables transformative microgrid topologies based on the adaptive operation of distributed VSC controllers towards resilient power grids with high penetration of renewables.
Keywords: Voltage source converter; point of common coupling; Distributed energy resource; Microgrid; Model predictive control